159 Prediction rediction of benefit from consolidation chemotherapy for cervical cancer patients using a clinical prognostic score. (18th September 2019) - dos Santos, A; Fabri, V; Queiroz, AC; Mantoan, H; Sanches, S; Guimarães, A; Ribeiro, A; Souza, R; Maya, J; Santos, E; Castro, F; João Paulo, L; et al.
Abstract : Objectives: The use of consolidation chemotherapy (CCT) after chemoradiation (CRT) in cervical cancer remains debatable. We evaluated the impact of CCT added to up-to-date CRT (CRT) and sought to identify predictive factors of CCT benefit. Methods: This retrospective study reviewed 216 patients with 2014 FIGO stage IB2-IIA2, and IIB-IVB (para-aortic nodes only) cervical cancer treated with CRT alone or CRTT followed by CCT (CCT group). Firstly, we assessed the prognostic role of CCT. Moreover, we developed a prognostic score for distant metastasis free survival (DMFS). Results: After 42.8 months of median follow up 174 patients were treated with standard CRT and 72 with CCT. Clinical characteristics were comparable between groups, except CCT patients were younger (p<0.001) and less frequently treated with 3D radiation techniques (81.4% vs 93.1%, p=0.023). Median survivals were not reached in both groups. In multivariate analyses, CCT was related to longer overall survival (OS) (HR 0.35, p=0.023), progression free survival (HR 0.41, p=0.005) and DMFS (HR 0.40, p=0.010) but not locoregional control.Potential negative factors for DMFS included lymph node status, adenocarcinoma histology, and stage III or IV and formed a four-tier score (0 to 3 points) with good discrimination (p<0.001) (p=0.001). CCT was associated with longer OS (p=0.014) and DMFS (p=0.023) among patients with a score >1 but not for patients with score ≤1 (OS: p=0.310; DMFS: p=0.179). Conclusions: A clinical score may predict CCT benefit. If this score withstands external validation, it may contribute to better selection for CCT.